Análisis de modelo de conservación para el mantenimiento de las vías urbanas en la ciudad de Daule - Martínez Veloz, Gustavo Tomas (2025)
The thesis "Analysis of the Conservation Model for the Maintenance of Urban Roads in the City of Daule" addresses the problem of road maintenance in Daule, Ecuador, and proposes improvements to optimize the management of urban road infrastructure. The study is based on an exhaustive analysis of the current situation of Daule's urban roads, identifying the main challenges facing the current conservation model. These challenges include the lack of adequate financial resources, inefficient planning of maintenance activities, and the absence of innovative technologies to improve the efficiency and quality of road maintenance. Through literature review, data analysis and consultations with experts in the field of road maintenance, areas of opportunity have been identified to improve the conservation model and optimize the maintenance management of urban roads in Daule. These areas include the implementation of a road asset management system, the prioritization of preventive maintenance over corrective maintenance, the adoption of innovative technologies, the strengthening of technical and administrative capacities, the promotion of citizen participation, and the establishment of strategic alliances. with public and private institutions..............